Defect passivation through quick radiative annealing for high-performance solution-processed Al-doped ZnO TCOs - Kumar A.; Gorai D.K.; Ahmad M.I. (My University, 2025)
Solution-processed ZnO-based TCOs generally exhibit greater resistivity and lesser transparency when compared to those processed by vapour-based techniques such as sputtering, PLD or ALD. This is mainly because of defects, lack of preferred orientation, partial segregation of dopants near grain boundaries and sometimes impurities such as partially decomposed precursors. The properties can be improved by improving crystallinity and reducing scattering from grain boundaries and defects, improving mobility. Doping with aluminium increases the carrier concentration; however, it introduces defects that hamper transparency and mobility. Here, we have utilized quick radiative annealed (10 s at 480°C) in 5%H2+Ar atmosphere to achieve resistivity as low as ~ 2 × 10− 3 Ωcm with ~ 94% transparency at 550 nm wavelength for 2% Al-doped ZnO films in spray-deposited thin film. The fast radiative annealing improved the mobility of all the films while simultaneously increasing the carrier concentration by as much as 10 times. XRD and SEM showed improved orientation and crystallinity on quick radiative annealing. PL and Raman spectroscopy revealed that the hydrogen passivated the defects (Zni and VO) and grain boundaries resulting in improved mobility and transparency. XPS and UV visible spectroscopy revealed activation of greater amounts of Al dopants, at the same time, passivating VO by partial H+ substitution, increased carrier concentration and wider optical bandgaps. © 2023, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.